(untitled) (Journal of the College of Basic Education, 2022)
The development of research in the field of arts at the local and global level led to the recognition of the importance and value of evaluation of the practical aspects, due to the importance of the skills that the learner acquires during the practice of art, and this is what prompted the two researchers to enter this field because of its scientific importance in standing on aspects of shortcomings and correcting them and aspects of strength and praise. In it, she established a model for the problem of her research to evaluate the productions of students of the Department of Advertising Techniques in the subject of directing and colors. The current research aims to